EDUCATIONAL FUNCTIONS OF HISTORICAL DOCUMENTS (Pedagogy of Higher and Secondary Education, 2004)
The article is about educational functions which the historical documents play in the educational process. On the basis of these documents the author has made the systematization of the methods of the way of the analyze and the systematization of using of written historical sources of knowledge with the purpose to raise the pupils ’ knowledge activity and of the efficiency of the education at the history lessons.